DESIGN, IMPLEMENTATION, AND INSTALLATION OF SOLAR POWER ENERGY FOR BLOCK OF OFFICES: A CASE STUDY OF COMPUTER SCIENCE DEPARTMENT - Ayomiku John Olatunji (World Journal of Biology Pharmacy and Health Sciences, 2026)
The persistent challenges of unreliable grid electricity and the environmental impacts of diesel generator reliance in Nigeria’s academic institutions necessitate the exploration of sustainable energy solutions. This study focuses on the design, implementation, and installation of a solar-powered system to provide reliable energy to five lecturers' offices within the Computer Science Department at the Federal University of Petroleum Resources, Effurun. The system integrates twelve high-efficiency 450W monocrystalline solar panels, a 10kVA hybrid inverter with a built-in Maximum Power Point Tracking (MPPT) charge controller, and four 220Ah 12V tubular batteries connected in series. The methodology adopted an Agile, iterative approach to adapt to evolving load requirements, ensuring uninterrupted power for a minimum of five hours daily. The total hourly energy demand of 2.39 kWh was successfully met by the system's 5.4 kW peak generation capacity. Performance evaluations revealed that the system operates at 85-90% efficiency on sunny days, yielding 8-10 kWh/day. On cloudy and rainy days, output drops significantly, but the 10.56 kWh battery bank provides sufficient supplementary power to maintain uninterrupted office operations. The results demonstrate that the solar-powered system effectively mitigates energy reliability issues, reduces long-term operational costs, and minimizes environmental pollution compared to diesel alternatives. This study underscores the technical feasibility and ecological significance of renewable energy adoption in institutional settings.